Long-term monitoring of aquatic birds wintering in the Romanian Prut River basin - GACHE Carmen (Scientific Annals of the Danube Delta Institute, 2006)
Beginning with the winter of 1992, we performed a continuous ornithological survey in different wintering areas belong the Prut River basin. We took in our attention the most important dam lakes, fishponds and some observatory points on the Prut River valley. We created a database about the trend and the actual situation of waterfowls’ population in this part of Romania, identifying the best sites for birds’ during the cold season and monitoring the activities that disturb the birds’ life, estimating the human pressure level in these areas. The wintering avifauna is formed by 100 birds’ species (43,85% from the total avifauna of Prut River basin – 228 species), 31 being aquatic birds – 21 species belonged to the order Anseriformes. The hiemal appearance (November – February/March in the last years of our study) of Prut River basin showed thousands of geese and ducks that represents the numerically most representative birds’ group of the winter avifauna, followed by Coot (Fulica atra). We followed the global contribution of these species to the total wintering waterfowls’ population, during the whole period of study